Perancangan Aplikasi Game “DEFENSE BODY” Sebagai Media Edukasi Kesehatan Untuk Anak-anak - Fairuz Zuyyina; Aileena Solicitor C.R.E.C.; Widyasari (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2021)
Most sources of disease come from dirty items. Dirty items usually have lots of disease-causing bacteria and viruses that can lower our immune system. One of the reasons is unhygienic food. For that, we need interesting and informative educational media in the form of an educational game application